Granular cell ameloblastoma: A rare and unique variant (Indian Journal of Case Reports, 2024)
Ameloblastoma is a slow-growing and locally invasive epithelial odontogenic tumor of the jaw that runs a benign course in most cases. Granular cell ameloblastoma is a rare subtype of ameloblastoma, showing the granular transformation of its cytoplasm. It is considered as an aggressive variant of ameloblastoma. Herein, we report the case of a 34-year-old male patient who presented with a swelling in the left cheek for a 1-year duration with a recent rapid increase in size. Examination showed a 4 × 3 cm growth involving the left buccal mucosa and retromolar area. Imaging studies showed expansile lytic lesion mandible. Biopsy revealed neoplasm with odontogenic epithelial islands showing peripheral palisading of tall columnar cells with reversal of polarity and the center of the islands showing stellate reticulum-like cells which were markedly replaced by granular cells. Granular cells can appear in various odontogenic and non- odontogenic tumors. When there is extensive granular cell change in ameloblastoma, it should be differentiated from other oral lesions with granular cells including granular cell odontogenic tumor, granular cell tumor, and congenital epulis. Herein we report the case of a 34-year-old male patient presented with swelling left cheek of one-year duration with recent rapid increase in size. Examination showed a 4x3 cm growth involving left buccal mucosa and retromolar area. Imaging studies showed expansile lytic lesion mandible. Biopsy revealed neoplasm with odontogenic epithelial islands showing peripheral palisading of tall columnar cells with reversal of polarity and the center of the islands showing stellate reticulum like cells which were markedly replaced by granular cells. Granular cells can appear in various odontogenic and nonodontogenic tumors. When there is extensive granular cell change in ameloblastoma it should be differentiated from other oral lesions with granular cells including granular cell odontogenic tumour, granular cell tumour and congenital epulis.